Problems and resolutions in dealing with waste disposable paper cups. (1st March 2018) - Ma, Yuhui
In recent years, the problem caused by waste disposable paper cups (WDPCs) has became a topic of great concern to scientists, and commercial companies have also begun to take an interest in developing processes for tackling the issue. In this review, the inherent problems and social barriers during the recycling of WDPCs are described. This review presents the major conclusions of previously published works focused on the utilisation of WDPCs for material and energy purposes. The commercial utilisation of WDPCs is also described. Some suggestions for better recycling of WDPCs are given in the final part of this work.